Kinematic study of the relation between the instantaneous center of rotation and degenerative changes in the cervical intervertebral disc - Liu, Baoge; Liu, Zhenyu; VanHoof, Tom; Kalala, JeanPierre; Zeng, Zheng; Lin, Xin (European spine journal, 2014)
Purpose We located the instantaneous center of rotation (ICR) for the cervical spine at various ages and investigated age-related changes. We evaluated the impact of cervical disc degeneration on the ICR using a scoring system based on plain radiographs. Methods Flexion, extension, and neutral lateral radiographs were obtained from 680 asymptomatic subjects (363 men, 317 women; ages 20–79 years) divided into six 10-year-age groups. The ICRs from C3/C4 to C6/C7 were determined from the radiographs using MIMICS software. A scoring system determined from lateral radiographs quantitatively assessed degeneration of cervical intervertebral discs. ICRs were compared among groups to analyze age-related changes and the relation between degenerative changes and ICR location. Results In asymptomatic subjects, the ICR was located approximately at the superior half of the lower vertebral body height and the posterior half of its width. The ICR at the C5/C6 level was located more anterior and higher in patients >50 years than in younger subgroups ( P < 0.05). Degenerative changes produced more anterosuperior translation of the ICR, which was significantly correlated with height loss ( P < 0.05). In moderately or severely degenerated segments, the ICR location change reached statistical significance ( P < 0.05). Conclusions Baseline data for Chinese cervical spine ICRs were established for the third through eighth decade of life, including age-related changes and the kinematic effects of degenerative change on the ICR in the functional spine unit. These findings should be considered in clinical practice and when designing disc prostheses.